KEWIRAUSAHAAN BERBASIS PERTANIAN DI DESA HATOGUAN KECAMATAN PALIPI KABUPATEN SAMOSIR - Napitupulu, Runggu Besmandala; Hutabarat, Lamminar; Silaen, Novia Ruth; Tarigan, Jenni (PKM Maju UDA, 2024)
Community service activities aim to create successful entrepreneurs and provide knowledge about the steps to starting a business in agriculture. The problem faced is the character of the Hatoguan village community who are surrendered to their current situation. They are more demanding of the government in meeting their needs. The PkM team motivated the participants by transferring knowledge about entrepreneurship in agriculture, especially cultivation/plantation and fisheries. The activity was carried out for 3 (three) months starting from observation to evaluation. Participants were very enthusiastic about the material provided. The village head is very collaborative with the PkM team. The results of the evaluation show that the above activities have an impact on the community. Some of the participants have started a new business. They are also in the process of establishing a institution for the production and distribution of maize agricultural.